Nivolumab-induced capillary leak syndrome associated with chylothorax in a melanoma patient: A case report and review of the literature - Neuville, Carole; Aubin, François; Puzenat, Eve; Popescu, Dragos; Crepin, Thomas; Nardin, Charlée (Frontiers in Oncology, 2022)
Introduction: Adverse events (AEs) of immune checkpoint inhibitors (ICIs) are frequent and mainly due to an overactivity of the immune system leading to excessive inflammatory responses (immune-related AE) that can affect any organ of the body. Beside the most frequent AEs, there are rare AEs for whose diagnosis and treatment can be challenging. We report here a singular case of capillary leak syndrome associated with chylothorax occurring in a patient who has been treated with adjuvant nivolumab (anti-PD1) for resected AJCC stage IIB primary melanoma. Case presentation: A 43-year-old woman was diagnosed with a nodular stage IIB melanoma of her left thigh, according to the AJCC 8th edition (T3bN0M0). The woman was treated with adjuvant nivolumab. She stopped the treatment after 4 infusions due to thrombopenia. Three months later, she developed facial and leg edema and ascites due to capillary leak syndrome. The capillary leak syndrome was associated with chylothorax and elevated anti-vascular endothelial growth factor. The patient was initially treated with several pleural puncturing and steroids. Capillary leak syndrome and chylothorax progressively decreased with intravenous immunoglobulins and fat-free diet without recurrence of melanoma at one-year follow-up. Conclusion: capillary leak syndrome is a rare and potentially life-threatening AE of ICIs such as anti-PD1. This AE may be associated with chylothorax probably related to lymphatic permeability induced by anti-PD1.